Pengendalian Banjir Pada Daerah Aliran Sungai Pesanggrahan Menggunakan Pemodelan HEC-RAS - Habibi, Naufal Ilham; Darmawan, Yahya (Universitas Budi Luhur, 2024)
Flooding is one of the most common threats in Indonesia. The disaster generally occurs during the rainy season due to high rainfall. The inability of the watershed to accommodate the rain causes the water to overflow and inundate the surrounding area. The Pesanggrahan watershed is one example with a dense population. This hampers activities, economic losses, and health problems. Efforts are needed to prevent flood disasters. One of them is flood modelling using HEC-RAS. The purpose of the research focuses on the application of the HEC-RAS model in the Pesanggrahan watershed to determine the boundaries of water levels and overflows that have the potential to flood. The benefit of the research is to control flooding. The research was conducted in the Pesanggrahan watershed with coordinates of 6o 10' 20